2‐ and N6‐functionalized adenosine‐5′‐diphosphate analogs for the inhibition of mortalin. Issue 15 (18th June 2019) - Moseng, Mitchell A.; Nix, Jay C.; Page, Richard C.
Abstract : Our early efforts to find a covalent inhibitor of mortalin, a member of the 70 kD heat shock protein (Hsp70) family, led us to solve the structure of the mortalin nucleotide‐binding domain (NBD) in complex with N6‐propargyladenosine‐5′‐diphosphate. The acquired structure emphasizes the ability of the nucleotide‐binding pocket to accommodate modified ADP compounds. A library of ADP analogs modified at either the 2‐ or N6‐positions of adenosine was screened against the mortalin‐NBD. Competitive inhibition and binding assays of the analogs demonstrate that modifications at the 2‐ or N6‐positions have potential to bind and inhibit mortalin uniquely compared to other Hsp70 homologs, and that modifications at the 2‐position confer the greatest selectivity in binding and inhibition of the mortalin‐NBD. Abstract :